Investigating fishing strategies and habitat differences in late Holocene Oregon Coast sturgeon (Acipenser spp.) through coupled genetic and isotope analyses - Emma A. Elliott Smith; Torben C. Rick; Courtney A. Hofman (Quaternary Science Advances, 2022)
Understanding the habitats people were fishing in the past is central to evaluating the relationship between coastal environmental change and human behavior. Researchers often use zooarchaeological identification of fishes and modern ecological data to infer the habitats people fished in the past. However, these inferences assume stable environmental conditions through time and can be hindered by precision issues in identification of archaeological specimens (species vs. genus or family). Here, we integrate genetic and bulk tissue stable isotope data to investigate a late Holocene sturgeon fishery in northern Oregon. Ancient DNA analysis indicated that people were fishing for both green and white sturgeon (Acipenser medirostris and Acipenser transmontanus) in comparable numbers. Stable isotope analyses of these same bones documented distinct isotope values for each species, correlating with species-specific habitat preferences. These findings highlight the value of paired isotope and genetic data to elucidate human fishing strategies and environmental change and provide baseline ecological data for modern fisheries.